Plastic part design for injection molding : an introduction - Malloy, Robert A., ....- (Munich : Hanser Publishers ; Cincinnati, Ohio : Distributed in the USA and in Canada by Hanser Publications, 2011)
The goal of the book is to assist the designer in the development of parts that are functional, reliable, manufacturable, and aesthetically pleasing. Since injection molding is the most widely used manufacturing process for the production of plastic parts, a full understanding of the integrated design process presented is essential to achieving economic and functional design goals. Features over 425 drawings and photographs. Contents: Introduction to Materials. Manufacturing Considerations for Injection Molded Parts. The Design Process and Material Selection. Structural Design Considerations. Prototyping and Experimental Stress Analysis. Assembly of Injection Molded Plastic Parts. Conversion Constants.
Keywords: Engineering design; Injection molding of plastics; Machine parts